Gender Differences in the Recognition of Emotional States - Barabanschikov V.A; Suvorova E.V (Moscow State University of Psychology and Education, 2022)
As a rule, gender differences in the perception of human emotional states are studied on the basis of static pictures of face, gestures or poses. The dynamics and multiplicity of the emotion expression remain in the «blind zone». This work is aimed at finding relationships in the perception of the procedural characteristics of the emotion expression. The influence of gender and age on the identification of human emotional states is experimentally investigated in ecologically and socially valid situations. The experiments were based on the Russian-language version of the Geneva Emotion Recognition Test (GERT).83 audio-video clips of fourteen emotional states expressed by ten specially trained professional actors (five men and five women, average age 37 years) were randomly demonstrated to Russian participants (48 women and 48 men, Europeans, ages ranged from 20 to 62 years, with a mean age of 34 (SD = 9,4).It is shown that women recognize multimodal dynamic emotions more accurately, especially those which were expressed by women. Gender and age differences in identification accuracy are statistically significant for five emotions: joy, amusement, irritation, anger, and surprise. On women's faces, joy, surprise, irritation and anger are more accurately recognized by women over 35 years of age (p<0,05).On male faces, surprise is less accurately recognized by men under 35 (p<0,05); amusement, irritation, anger - in men over 35 (p<0,05). The gender factor of perception of multimodal dynamic expressions of the state acts as a system of determinants that changes its characteristics depending on a specific communicative situation.